Auditory Mismatch Negativity Under Predictive Coding Framework and Its Role in Psychotic Disorders - Fong, Chun Yuen; Law, Wai Him Crystal; Uka, Takanori; Koike, Shinsuke (Frontiers in Psychiatry, 2020)
Traditional neuroscience sees sensory perception as a simple feedforward process. This view is challenged by the predictive coding model in recent years due to the robust evidence researchers had found on how our prediction could influence perception. In the first half of this article, we reviewed the concept of predictive brain and some empirical evidence of sensory prediction in visual and auditory processing. The predictive function along the auditory pathway was mainly studied by mismatch negativity (MMN) – a brain response to an unexpected disruption of regularity. We summarised a range of MMN paradigms and discussed how they could contribute to the theoretical development of the predictive coding neural network by the mechanism of adaptation and deviance detection. Such methodological and conceptual evolution sharpen MMN as a tool to better understand the structural and functional brain abnormality for neuropsychiatric disorder such as schizophrenia.